Taboo Words In The Youtube Law & Crime Network Of The Freak Off Party Case By P.Diddy: A Sociolinguistics Study - Silvia Sandi; Ervina Cm Simatupang (Universitas Nahdlatul Wathan Mataram, 2025)
The research aims to classify types of taboo language and examine its media functions relevant to the